PERAN AMERIKA SERIKAT DALAM PEMBERANTASAN PEROMPAKAN BERSENJATA DAN PEMBAJAKAN SOMALIA 2008-2012 - Lubis, Susi; Hanura, Marten; Susetianingsih, Hermini (Journal of International Relations, 2015)
Armed robbery and piracy conducted by Somali pirates in the Horn ofAfrica region are international crime which threatens internationalpeace and security. These crimes have raised international concerns.In response to the threats, The United Nations Security Council issuedResolution No. 1851 that stressed the importance of the state,regional, and international organizations to actively fight piracy andarmed robbery. Responding to the resolution, the United Statesbecame one of the nations that response to these crimes; by issuingforeign policy that contains a variety of efforts in combating armedrobbery and piracy in the region. This research aims to determine therole of United States to overcome Somali armed robbery and piracy inthe Horn of Africa.This research uses theory of international crime, national insecurity,international actors, and foreign policy. This is analytical descriptiveresearch. Data collected by interview as well as related literatures.The result of this research shows that United States as direct centralactor lead the international actions to combat Somali armed robberyand piracy in the Horn of Africa Region by doing â€œsmart powerâ€approach.